Identify the successful story of the indigenous ammatoa community preserving the environment - Chotimah, Chusnul; Suprianto, Bibi (Journal of Critical Ecology, 2026)
Background: This study explores how the Ammatoa indigenous community demonstrates the capacity to preserve indigenous land and forest through indigenous knowledge practice, a result of a dialectical process between their traditional knowledge based on Pasang ri Kajang with non-traditional knowledge such as modernism. The dialectical process could be seen in how they practice indigenous tourism, which is a part of the modern industry. The indigenous tourism that uses the indigenous recognition as an authoritative foundation attracts more visitors that increasing not only their economic income but also their social and political position. Methods: Using a qualitative approach through library research based on theses, reports, and relevant documents, this study examines how the Ammatoa community obtains recognition as an indigenous community. Findings: The findings reveal that formal state recognition as an indigenous community requires multiple internal and external factors, particularly those related to policy frameworks and political dynamics. Two key strategies emerge: the development of cultural tourism as a form of asserting territorial rights, and the advocacy for legal recognition of customary land to prevent state acquisition. Conclusion: These findings show that indigenous knowledge, tourism development, and legal recognition are interrelated processes in securing indigenous rights and sustaining environmental stewardship. Novelty/Originality of this article: This article offers several original contributions that align strongly with the journal’s aims and scope in advancing interdisciplinary ecological discourse and environmental justice.